Metrica orale e tradizione scritta: l’esempio dei wechsell neidhartiani - Teresa Proto (Filologia Germanica, 2024)
ORAL METER AND WRITTEN TRADITION: THE EXAMPLE OF NEIDHART’S ‘WECHSELL’. The present paper deals with a group of songs – the so-called wechsell – handed down with music in MS Berlin, Staatsbibliothek zu Berlin – Preußischer Kulturbesitz, Ms. Germ. Fol. 779 (MS c, ca. 1460) and attributed to the 13th-century poet Neidhart. The analysis of the songs is developed within a framework that combines Zumthor’s theoretical assumptions concerning the oral nature of medieval literature and the use of performance models elaborated in the fields of ethnomusicology and folklore studies. It is suggested that explorations of the performance of analogous expressions in contemporary traditions may provide a potential for new perspectives on medieval poetry and help develop an analytical matrix for the understanding of earlier texts